KEGIATAN WALL CLIMBING SEBAGAI PENANAMAN RASA PERCAYA DIRI PADA ANAK USIA DINI: Rasa Percaya DIri Pada Kegiatan Wall Climbing - Wulansari, Betty Yulia; Rahmawati, Ida Yeni; Aziza, Rizqia Putri (Jurnal Ilmiah POTENSIA, 2025)
Self-confidence is essential for a child's development and should be fostered from an early age. It is an attitude of certainty in one's abilities and pride in one's accomplishments. Nurturing self-confidence in early childhood is crucial for their future development. This study explores how wall climbing activities can promote self-confidence in young children. Wall climbing is a physical activity, sometimes considered an extreme sport, that involves scaling an artificial wall with artificial rock formations serving as handholds and footholds. Participating in wall climbing offers numerous benefits for young children, including building self-confidence. This qualitative study employed observation, interviews, and documentation to collect data. The research aims to investigate the role of wall climbing in fostering self-confidence in early childhood, identify factors that support children's self-confidence, and describe the challenges teachers face when implementing wall climbing activities at PAUD Sabila Ponorogo. The findings indicate that wall climbing can instill self-confidence in young children by fostering self-assurance, optimism, courage, a positive attitude, and initiative. Verbal encouragement from teachers and facilitators plays a vital role in supporting children's self-confidence, especially when they experience doubt or fear. A key challenge identified was the climbing wall's design, which was deemed unappealing and unsuitable for young children. Therefore, a redesign is recommended to make the wall more engaging and challenging for this age group